International Guidelines for the Diagnosis and Management of Hyperinsulinism - De Leon, Diva D. (2024)
Background: Hyperinsulinism (HI) due to dysregulation of pancreatic beta-cell insulin secretion is the most common and most severe cause of persistent hypoglycemia in infants and children. In the 65 years since HI in children was first described, there has been a dramatic advancement in the diagnostic tools available, including new genetic techniques and novel radiologic imaging for focal HI; however, there have been almost no new therapeutic modalities since the development of diazoxide.Summary: Recent advances in neonatal research and genetics have improved our understanding of the pathophysiology of both transient and persistent forms of neonatal hyperinsulinism. Rapid turnaround of genetic test results combined with advanced radiologic imaging can permit identification and localization of surgically-curable focal lesions in a large proportion of children with congenital forms of HI, but are only available in certain centers in "developed" countries. Diazoxide, the only drug currently approved for treating HI, was recently designated as an "essential medicine" by the World Health Organization but has been approved in only 16% of Latin American countries and remains unavailable in many under-developed areas of the world. Novel treatments for HI are emerging, but they await completion of safety and efficacy trials before being considered for clinical use.Key messages: This international consensus statement on diagnosis and management of HI was developed in order to assist specialists, general pediatricians, and neonatologists in early recognition and treatment of HI with the ultimate aim of reducing the prevalence of brain injury caused by hypoglycemia. A previous statement on diagnosis and management of HI in Japan was published in 2017. The current document provides an updated guideline for management of infants and children with HI and includes potential accommodations for less-developed regions of the world where resources may be limited.